Solidarity and Competition Among Gojek Drivers in Yogyakarta City - Dwirawati; Udasmoro; Budiawan (CV. Inara, 2021)
This article describes and analyzes the solidarity and competition among Gojek drivers in Yogyakarta. For data collection, it was carried out through observation, in-depth interviews, and documentation. The result shows that PT. Gojek Indonesia created groups based on their criteria. The groups formed by PT. Gojek were included in the office Whatsapp group. Arena, capital, and habitus are important elements to reveal that there is the classification of Gojek drivers' accounts based on priority, regular, and 'gagu'. In the Bourdieu paradigm, the cultural capital owned by Gojek drivers plays an important role in benefiting them in the arena, such as time discipline to find customers, driver performance, drivers who always accept incoming orders and never reject orders, customer rating, or good customer ratings, customer-friendly drivers, and smartphone proficiency that will give advantage in the competition. Thus, the result of mapping the arena of competition among Gojek drivers in Yogyakarta shows that drivers indirectly have to have some strategies in the 'game' of competition among Gojek drivers across several social arenas, namely economy, culture, and social.